Chronic Obstructive Pulmonary Disease and the frequent hospital readmissions : Can anything be done? - S. Gaude, G.; Hattiholi, J.; Chaudhury, A. (Scientific Journal of Medical Science, 2013)
Acute exacerbations of COPD (AECOPD) are known to be associated with increased morbidity and mortality and have a significant socioeconomic impact. The factors that determine frequent hospital readmissions for AECOPD are poorly understood. The aim of this study was to ascertain the factors responsible for the repeated admissions for AECOPD. We conducted a prospective study of 235 patients with COPD with one or more admissions for acute exacerbations in a tertiary care hospital. Frequency of previous readmissions for AECOPD in the past year, and clinical characteristics, including spirometry were ascertained in the stable state both before discharge and at 6-month post discharge. All the patients were followed up for a period of two years after discharge to evaluate the readmissions for the acute exacerbations. Among 149 COPD patients who were admitted and assessed for AECOPD, there were 278 readmissions for AECOPD over a follow-up period of 24 months. Of these, 27% had one readmission, while rest 78% had two or more readmissions during this period. There was a high prevalence of current or ex-heavy smokers, associated co-morbidity, underweight patients and low prevalence of vaccination and use of domiciliary oxygen therapy among COPD patients. A total of 15.4% mortality was observed in the present study. The multivariate logistic regression analysis for repeated admissions revealed that disease duration >10 years (OR =0.50; 95% CI: 0.27 -0.93), non-use of inhaled corticosteroids (ICS +LABA) (OR = 2.31; 95% CI: 2.26–4.88), lower serum albumin level (<2gm/dl) (OR = 0.48; 95% CI: 0.26–0.88), MRC dyspnea grade > 3 (OR = 1.15; 95% CI: 2.56–4.89), body mass index (BMI) <20 (OR =0.62, 95% CI: 0.31-1.23) and non-use of Tiotropium (OR = 1.21, 95% CI: 0.67-2.19) were independently associated with frequent readmissions for AECOPD. The repeated exacerbations in COPD were common with major burden to the society. The major factors influencing frequency of repeated COPD exacerbations were disease duration, non-prescription of inhaled corticosteroids (ICS +LABA) and Tiotropium, lower serum albumin level (<2gm/dl), lower BMI and MRC dyspnea grade > 3.